Historische Geographie und räumliche Planung - Denecke, Dietrich (ERDKUNDE, 1982)
Town- and country-planning has no doubt not only a prospective dimension but also an historical one. Though the application of geographical research in planning was discussed and practiced since the thirties, the development of a concept of an applied historical geography was neglected. Eight main fields of an applied historic - geographical research for planning are discussed in this paper: 1. The history of planning and the analysis of planned elements of the cultural landscape as a historical background for modern planning. 2. Identification, recording and mapping of historic landscapes and features. 3. Basic studies for planning of regional conservation and protection. 4. Research within the framework of preservation of rural settlements. 5. Basic studies in connection with restoration of old town -centres. 6. Research on criteria for the role of the visible past for environmental perception and planning: evaluation of the historic environment. 7. Recreational and educational use of the historic resources of historic landscapes and towns. 8. Design of prospective models of landscape and settlement development on the base of an analysis of historical processes. There is a good deal to be learned of the meaning and cultural value of contemporary cultural landscapes from the persistence of former landscapes, their making and shaping.